Protective Effect of Chrysanthemum morifolium cv. Fubaiju Hot-Water Extracts Against ARPE-19 Cell Oxidative Damage by Activating PI3K/Akt-Mediated Nrf2/HO-1 Signaling Pathway - Hao, Yiming; Li, Yanfang; Liu, Jie; Wang, Ziyuan; Gao, Boyan; Zhang, Yaqiong; Wang, Jing (Frontiers in Nutrition, 2021)
Chrysanthemum morifolium cv. Fubaiju is a kind of widely consumed herb tea with multiple health benefits. The present study was aimed to evaluate the protective capacity of C. morifolium cv. Fubaiju hot-water extracts (CMs) against ARPE-19 cell oxidative damage. The results showed that pretreatment with 100 μg/mL CM could significantly reduce cell oxidative damage and apoptosis. Proapoptotic protein expression such as Bax, cleaved caspase-3, and cleaved poly(ADP-ribose) polymerase (PARP) was significantly decreased after CM addition, while the expression level of antioxidant enzymes including catalase, glutamate-cysteine ligase catalytic subunit (GCLc), superoxide dismutase 2 (SOD2), and NAD(P)H:quinone oxidoreductase 1 (NQO-1) was significantly promoted. Meanwhile, CM treatment upregulated Akt phosphorylation, nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear translocation, and the expression level of antioxidant gene heme oxygenase-1 (HO-1) in a dose-dependent manner under oxidative stress. Knockdown of Nrf2 by targeted small interfering RNA (siRNA) alleviated CM-mediated HO-1 transcription and almost abolished CM-mediated protection against hydrogen peroxide (H2O2)-induced cell damage. Correspondingly, the protective effect of CM was dramatically blocked after interference with phosphatidylinositol 3-kinase (PI3K)/Akt inhibitor LY294002, indicating that the protective effect of CM on cell oxidative damage was attributed to PI3K/Akt-mediated Nrf2/HO-1 signaling pathway.